Evaluation of a Hemagglutination Test for Human Leptospirosis - Sulzer, Catherine R. (1973)
An indirect hemagglutination test for the diagnosis of leptospirosis is described; the test uses a soluble antigen from serotype patoc to sensitize sheep erythrocytes which are then fixed with glutaraldehyde. Evaluation of this procedure indicates that it is more reliable than the conventional macroscopic agglutination test and, in contrast with both microscopic and macroscopic agglutination tests, is positive only with sera from persons with current leptospiral illness. The test is simple and convenient and sensitized fixed cells may be stored for at least a year. In comparison with the macroscopic and microscopic tests, only a single antigen is required.